Frontosphenoid Synostosis. Issue 1 (January 2015) - Bot, Gyang; Leshem, David; Shiran, Shelly I.; Ben-Shachar, Shay; Constantini, Shlomi; Roth, Jonathan
<x xml:space="preserve">Abstract</x> Abstract Nonpositional anterior plagiocephaly results commonly from unilateral coronal craniosynostosis. We present 2 patients of a rare cause of anterior plagiocephaly known as frontosphenoid synostosis. This condition is characterized by the absence of a harlequin eye (or the harlequin sign on computed tomography), which is usually present in unilateral coronal synostosis. We also observed no reduction in the ear-eye distance, which can distinguish it from coronal craniosynostosis.